Semarak Masyarakat Desa Sasak Panjang Pada Perayaan Hari Kemerdekaan - Latifah, Latifah; Yudiana, Yudi (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2023)
The celebration of independence day is a reflection of the people's gratitude for independence. In practice, the form of celebration is often injured by activities that actually tarnish the value of independence itself. Sasak Panjang village, Tajurhalang sub-district, Bogor is one of the villages that has a fairly large area, and is inhabited by residents who come from various different regions in Indonesia. The diversity of backgrounds of the residents in this village of course needs to be fostered and maintained a sense of togetherness. In fact, we still hear a lot of negative news about the occurrence of brawls between regions, the entrenchment of one ethnic group from a certain area feeling superior to other regions, the control of territory or land by a certain regional stronghold, etc. One of the anticipatory steps taken by the Sasak Panjang village government is organizing a carnival celebration, because it contains meaning, significance and important values ​​in uniting the nation and developing the level of creativity by involving all ages of the community and students who are carrying out Real Work Lectures.